An accounting review of athletes in ownership of basketball club assets - Kristina Puspitasari; Sasongko Budisusetyo; Zakiah Zakiah (STIE Perbanas Surabaya, 2019)
Sports are now growing as a business industry that can involve many parties interested in it. This study aims to determine the accounting treatment of athletes, recognized as club assets in the sport industry, particularly at Surabaya Fever Basketball Club. The unit of analysis is the management accountant and athlete management with both the primary and secondary data. The data were collected using interview, observation, and documentatition and analyzed by means of testing, categorizing, tabulating, and recombining the evidence. The use of this qualitative method approach is an answer that cannot be measured in numbers, but the indicator is the meaning of the context. The results show that Surabaya Fever Club recognizes the athlete as an asset and has fulfilled the asset classification. It is proven by the existence of economic benefits or services in the future. There is a useful life for the company originating from past transactions and is expressed in monetary units. In addition athletes are valued as intangible assets because they have economic benefits for the organization and are identified without physical form. Athletes meet the main characteristics, that is, can be further identified. However, there are no specific standards that state or discuss human resource assets.